2022
DOI: 10.3389/fpsyg.2022.800120
|View full text |Cite
|
Sign up to set email alerts
|

What makes the pipeline leak? Women’s gender-based rejection sensitivity and men’s hostile sexism as predictors of expectations of success for their own and the respective other gender group

Abstract: In academia, the proportion of women decreases with each career level. In this research, we examined how this so-called leaky pipeline relates to gender-based relative expectations of success. The participants were students from social sciences where women are the majority among students, such that it is more readily – but erroneously – inferred that gender discrimination is not an issue. We assumed that gender-based relative expectations of success should be predicted by two variables. Women students should e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Structural reasons as well as the impact of biases might account for the differences in performance scores and have been explored in relation to a gendered productivity gap [48], or productivity puzzle [49]. Women expect men to perform better—and men agree [41]. They deal with a mosaic of inequity in financial compensation, grant funding, publications, authorship, citations, and speaking roles [50], all of which seem to be more pronounced when adding race/ethnicity characteristics [12,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural reasons as well as the impact of biases might account for the differences in performance scores and have been explored in relation to a gendered productivity gap [48], or productivity puzzle [49]. Women expect men to perform better—and men agree [41]. They deal with a mosaic of inequity in financial compensation, grant funding, publications, authorship, citations, and speaking roles [50], all of which seem to be more pronounced when adding race/ethnicity characteristics [12,32].…”
Section: Discussionmentioning
confidence: 99%
“…Women, especially tenured women, are more likely to leave or consider leaving owing to poor workplace climate rather than concerns about work-life balance [ 19 ]. Attrition has led to the popular descriptions of a glass ceiling and leaky pipeline [ 41 , 42 ] a predominantly male academic work environment, where quality and potential are more often doubted in female candidates than in male candidates [ 43 , 44 ]. The comparatively early exit and/or late entry might be owing to dissatisfaction with pay and promotion opportunities [ 45 ] family obligations, which fall disproportionately on women [ 46 ], and motherhood [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Respondents were also asked to answer questions related to their individual characteristics, which were considered as related to the perception of gender stereotypes in previous literature (e.g., Carli et al, 2016 ; Branchefsky and Park, 2018 ; Ollrogge et al, 2022 ). First, they were asked to indicate their career stage, resulting in the four dummy variables Student, PhD student, Post-doc , and Professor .…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, both women and men full professors perceived a higher fit (van Veelen and Derks, 2022b ). Women undergraduate students think that men are more likely to pursue successful careers than women, indicating that those women students tend to attribute success at a later career stage to the social role of men (Ollrogge et al, 2022 ). In a qualitative interview study with professors, agentic (i.e., masculine) attributes were perceived as more important for individuals in the pre-tenure stages.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…That study found that women of color are more able to relate to the populations their organizations serve but feel less confident about their fundraising abilities. Ollrogge et al (2022) investigated expectations of women's success in the social sciences among students in the field. They found that, despite outnumbering men in the classroom and in the field, women are less confident of their ability to be successful in their careers and feel that men would be successful.…”
Section: Building the Pipelinementioning
confidence: 99%